Acute HIV Infection and CD4/CD8 Ratio Normalization After Antiretroviral Therapy Initiation. (1st December 2018) - Davy-Mendez, Thibaut; Napravnik, Sonia; Zakharova, Oksana; Kuruc, JoAnn; Gay, Cynthia; Hicks, Charles B.; Mcgee, Kara S.; Eron, Joseph J.
Abstract : Background: We estimated the effect of initiating virologically suppressive antiretroviral therapy (ART) during acute HIV infection versus chronic HIV infection (AHI vs. CHI) on CD4/CD8 ratio normalization. Setting: A prospective clinical cohort study. Methods: We included patients initiating ART with AHI and CHI between 2000 and 2015 and compared time from ART initiation to the first normal CD4/CD8 ratio (defined as CD4/CD8 ≥1) using Kaplan–Meier curves and multivariable Cox proportional hazards models. Patient time was censored at virologic failure, lost to follow-up, or death. We also characterized CD4, CD8, and CD4/CD8 trajectories over the first 3 years of ART. Results: The 1198 patients were 27% female and 60% African American, with a median age of 37 years (interquartile range 28–47) at ART initiation. The 83 AHI patients were more likely male, younger, and of white race, than CHI patients. After 2 years of suppressive ART, 70% of AHI patients achieved a normal CD4/CD8 ratio, compared to 6%–38% of CHI patients, with greater likelihood of normalization at higher baseline CD4 counts. Time to normalization was shortest among AHI patients, followed by CHI patients with higher baseline CD4. The adjusted hazard ratio for time to normalization for AHI patients compared to CHI patients with baseline CD4 >350 was 4.33 (95% CI: 3.16 to 5.93). Higher baseline CD4/CD8 ratio was also associated with time to normalization (adjusted hazard ratio 1.54; 1.46, 1.63, per 0.1 increase in ratio). Conclusions: Initiating ART during AHI at higher baseline CD4 cell counts and CD4/CD8 ratios was associated with shorter time to CD4/CD8 ratio normalization. Abstract : Supplemental Digital Content is Available in the Text.